Performance Evaluation of Solar Rooftop System - Apichart Yodkhuang; Atthapol Ngaopitakkul (My University, 2015)
In the recent trend of renewable energy, photovoltaic (PV) has gained a lot of attention from government and private investors due to reduction of technology cost and support policy from government. Number solar rooftop system in residential sector in Thailand has been rapidly increased in term of installing capacity in these last few years. So, this paper aims to study performance of solar rooftop system. Factors affecting generating capacity of solar panel has been taken into account such as climate, temperature and solar radiation. Three types of solar panel have been used in research: monocrystalline, polycrystalline and thin-film. To evaluate the effect of weather on solar rooftop system and maximum power generating, capacity power and energy that solar rooftop system can generat have been measured.
Keywords: Grid parity; Solar Power; Solar cable; Solar micro-inverter; Solar Radiation and Photovoltaics